Response surface methodology for evaluation of the effects of screw speed, feed moisture and xanthan gum level on functional and physical properties of corn half products - Gumusay, Ozlem Akturk; Seker, Mahmut; Sadikoglu, Hasan (ELSEVIER, 2019)
Effects of screw speed (100-300 rpm), feed moisture (37-47%) and xanthan gum (XG) level (0-1%) on the functional and physical properties of corn half products were investigated and optimized by using three-factor and three-level Box-Behnken design (BBD) under response surface methodology (RSM). Response variables are water absorption index (WAI), water solubility index (WSI), degree of gelatinization (DG), water activity (a,), specific volume and color properties of extrudates. Increased screw speed decreased WAI and aw values and increased WSI values significantly. Specific volume of half products was low for all extrusion combinations and negative correlated with screw speed, feed moisture and XG level. Lightness and yellowness of half products were increased with increases in screw speed, feed moisture and XG level. Low DG for all half products was obtained (46.33-63.36%) because of temperature under 100 C in last two zones in extruder. Desirability function approach was used to find the optimum extrusion conditions. The optimized combinations of extrusion conditions were found 300 rpm screw speed, 47% feed moisture and 0.44% XG content with a desirability value of 0.991. No significant difference was found between experimental data and predicted values.
Keywords: extrusion; starch; Hydrocolloid; Third generation snack; Box- Behnken design; SPENT GRAIN ADDITION; EXTRUSION CONDITIONS; SENSORY CHARACTERISTICS; PROCESS VARIABLES; CHEMICAL-AGENTS; RESIDENCE TIME; WATER ACTIVITY; SNACK FOODS; OPTIMIZATION; Food Science & Technology